2005
DOI: 10.1523/jneurosci.5269-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Positive Allosteric Modulator of the α7 Neuronal Nicotinic Acetylcholine Receptor:In VitroandIn VivoCharacterization

Abstract: Several lines of evidence suggest a link between the ␣7 neuronal nicotinic acetylcholine receptor (nAChR) and brain disorders including schizophrenia, Alzheimer's disease, and traumatic brain injury. The present work describes a novel molecule, 1-(5-chloro-2,4-dimethoxy-phenyl)-3-(5-methyl-isoxazol-3-yl)-urea (PNU-120596), which acts as a powerful positive allosteric modulator of the ␣7 nAChR. Discovered in a high-throughput screen, PNU-120596 increased agonist-evoked calcium flux mediated by an engineered var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
473
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(512 citation statements)
references
References 59 publications
30
473
3
Order By: Relevance
“…The fact that potentiation occurred within seconds and was reversible suggests that incorporation of receptors, whether newly synthesized or drawn from intracellular stores, seems an unlikely explanation. As has been proposed for the potentiating effect of certain compounds on other nAChRs (Conroy et al 2003;Curtis et al 2002;Hurst et al 2005;Krause et al 1998;Zwart et al 2002), the most likely interpretation of the present results is that ryanodine acts as a positive allosteric effector, recognizing a specific binding site within the receptor protein. Another formal possibility is that ryanodine is having its effect through Fconformational coupling_ between hair cell AChRs and ryanodine receptors (RyR) as occurs during calcium release from sarcoplasmic reticulum in skeletal muscle.…”
Section: Figsupporting
confidence: 79%
“…The fact that potentiation occurred within seconds and was reversible suggests that incorporation of receptors, whether newly synthesized or drawn from intracellular stores, seems an unlikely explanation. As has been proposed for the potentiating effect of certain compounds on other nAChRs (Conroy et al 2003;Curtis et al 2002;Hurst et al 2005;Krause et al 1998;Zwart et al 2002), the most likely interpretation of the present results is that ryanodine acts as a positive allosteric effector, recognizing a specific binding site within the receptor protein. Another formal possibility is that ryanodine is having its effect through Fconformational coupling_ between hair cell AChRs and ryanodine receptors (RyR) as occurs during calcium release from sarcoplasmic reticulum in skeletal muscle.…”
Section: Figsupporting
confidence: 79%
“…Therefore, to probe for a specific involvement of α7* nAChRs in this process, we employed PNU-120596, an α7* nAChRs selective positive allosteric modulator. 31,32 In WT mice primed by SubSD, acute systemic PNU-120596 produced cellular changes of VTA DA neurons (Figures 4a-c) that are comparable to neuroadaptations induced by SD. Indeed, VTA DA neurons of SubSD mice pretreated with PNU-120596 exhibited increased in vitro excitability and AMPA.R/NMDA.R ratio (Figures 4a and b, respectively), as well as increased in vivo firing frequency and bursting activities (Figure 4c and Supplementary Figure S4c).…”
Section: Stress and Nicotine Detrimental Interplay C Morel Et Almentioning
confidence: 86%
“…Indeed, studies have shown that drugs activating muscarinic or nicotinic acetylcholine receptor (nAChR) subtypes have potential for the treatment of cognitive symptoms in patients with schizophrenia (for review, see Jones et al, 2012). Specifically, nicotine, as well as agonists and positive allosteric modulators of a7 and a4b2 nAChRs, attenuate various cognitive deficits in rodent models of schizophrenia (Boess et al, 2007;Hashimoto et al, 2008;Hauser et al, 2009;Hurst et al, 2005;Pichat et al, 2007;Rushforth et al, 2011;Thomsen et al, 2009;Timmermann et al, 2007;Wallace et al, 2011;Wildeboer and Stevens, 2008;Wishka et al, 2006). Our observations that nicotine reverses the selective CMOR impairment in rats treated with subchronic NMDAR antagonists is consistent with studies using standard object recognition tasks and extends these findings by implicating nAChRs in the potential treatment of multisensory integration deficits in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%